Synthesis and investigation on photophysical and photochemical properties of 7-oxy-3-methyl-4-phenylcoumarin bearing zinc phthalocyanines - Piskin, Mehmet; Durmuş, Mahmut; Bulut, Mustafa (Pergamon-Elsevier Science Ltd, 2012)
The synthesis of peripherally and non-peripherally tetrakis-(7-oxy-3-methyl-4-phenylcoumarin) and peripherally octakis-[tetrachlorotetra-(7-oxy-3-methyl-4-phenyl coumarin)] substituted zinc(II) phthalocyanines are performed and characterized for the first time in this study. The new compounds show excellent solubility in organic solvents, which makes them candidates for use in different applications. Photophysical (fluorescence quantum yields and lifetimes) and photochemical (singlet oxygen generation and photodegradation under light irradiation) properties of these novel coumarino phthalocyanines are investigated in dimethylformamide (DMF). The effects of the positions (peripheral or nonperipheral) of the substituents on the photophysical and photochemical parameters of the coumarino zinc(II) phthalocyanines are reported. The fluorescence quenching behavior of the studied zinc(II) phthalocyanines by addition of 1,4-benzoquinone (BQ) are also described. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Zinc(II) phthalocyanine; Coumarin (2H-chromen-2-one); Photophysical; Photochemical; Singlet oxygen